Acanthobdella peledina Grube 1851 - Carle, Danielle Božena De; Gajda, Łukasz; Bielecki, Aleksander; Cios, Stanisław; Cichocka, Joanna M.; Golden, Heidi E.; Gryska, Andrew D.; Sokolov, Sergey; Shedko, Marina Borisowna; Knudsen, Rune; Utevsky, Serge; Świątek, Piotr; et al. (Zenodo, 2022)
POPULATIONS OF A. PELEDINA The present evidence suggests that A. peledina from Alaska is distinct, to some degree, from European samples. However, Siberia and the Russian Far East have not been adequately sampled genetically for A. peledina . Accordingly, it is difficult to determine the genetic variability and population structuring of this species. Coupled with increased taxon sampling, additional genetic sampling of Alaskan populations could help to indicate whether they are a unique species or population. Sampling of quickly evolving nuclear loci or, ideally, next generation sequence data (e.g. RADSeq) would be useful for determining whether gene flow exists between the Alaskan and Nordic localities. Unfortunately, COI , the most common marker for determining differences between leech species and populations (de Carle et al. , 2017; Tessler et al. , 2018c; Mack et al. , 2019), and additional nuclear loci did not amplify for these samples, potentially leading to some issues with missing data. Furthermore, given that no external morphological differences were noted between samples of Nordic and Alaskan A. peledina , we refrain from formal species or population delimitation analyses at this time. Nevertheless, the fact that the Alaskan population is sister to, and genetically divergent from, the Nordic samples suggests that this is not an invasive or nonnative species that was translocated only in recent times by humans, which would have been plausible given that the first records of this species in Alaska came from the 1970s (Holmquist, 1974; Hauck et al. , 1979) and that it has not officially been reported since then, despite the clear importance of these American animals. The Nordic populations are fairly similar genetically, despite being sampled from multiple (albeit geographically close) countries. The maximum genetic distance at the COI locus is 1.52%, which is below the average value (~2.4%) typically reported for species of Hirudinea (Kvist, 2015; de Carle et al. , 2017; Anderson et al. , 2020; Mack et ...